A Probe-Compensated Helicoidal NF-FF Transformation for Aperture Antennas Using a Prolate Spheroidal Expansion - Amedeo Capozzoli; Claudio Curcio; Giuseppe D'Elia; Flaminio Ferrara; Claudio Gennarelli; Rocco Guerriero; Angelo Liseno (International Journal of Antennas and Propagation)
A new probe-compensated near-field-far-field (NF-FF) transformation for aperture antennas in a cylindrical scanning geometry is presented. Such a technique takes the advantage of the NF data acquisition made according to a very efficient sampling strategy along a helix and exploits a proper aperture field expansion based on the use of the prolate spheroidal wave functions (PSWFs), accounting for the a priori information on shape and size of the antenna under test. The unknown aperture field expansion coefficients of the PSWFs are evaluated from the acquired voltage samples by an inversion process using a regularized version of the singular value decomposition method. Experimental results on connected and disconnected radiating aperture antennas, including sum and difference patterns, show the effectiveness of the approach and, in particular, how it enables a serious reduction of the measurement points without impairing the FF estimation accuracy.